﻿Evaluation of xanthine oxidase inhibitory, antioxidative activity of five selected Papua medicinal plants and correlation with phytochemical content - Septriyanto Dirgantara; Muhamad Insanu; Irda Fidrianny (Pensoft Publishers, 2022)
Some medicinal plants from Papua have been used traditionally as hyperuricemia and antioxidant agents for many ethnic in Papua Islands. The present study aims to evaluate inhibitory xanthine oxidase, antioxidative activities, total phenolic, and total flavonoid of five Papua selected medicinal plants, Myrmecodia beccarii, Villebrunea rubescens, Breynia cernua, Bridelia spp. and Dodonaea viscosa. Preliminary phytochemical screening revealed the presence of flavonoids and phenolic compounds with TLC-densitometric analysis, which is responsible for the biological activities of different plant extracts. Antioxidant was tested by 2,2- diphenyl-1- picrylhydrazyl (DPPH) and cupric ion antioxidant capacity (CUPRAC) methods and expressed as the Antioxidant Activity Index (AAI). Xanthine oxidase inhibitory (XOI) activity was evaluated by a spectrophotometer. The ethyl acetate of Myrmecodia beccarii extract (MEA) showed the highest antioxidative and XOI activity. The MEA extract from Papua may be developed as a new potential source of antioxidant and xanthine oxidase inhibitory agent.